An unprecedented cobalt(ii)-containing Wells–Dawson-type tungstovanadate-based metal–organic framework as an efficient catalyst for ring-opening polymerization of ε-caprolactone. Issue 21 (15th May 2020) - Shen, Nan; Tian, Feng; Chang, Jun; Huang, Kun-Lin; Zhang, Zhi-Hui; Feng, Xuejun; Gu, Jiande; Chen, Sheng-Chun; He, Ming-Yang; Chen, Qun
Abstract : An unprecedented organic–inorganic hybrid material based on Wells–Dawson-type tungstovanadate building blocks and cobalt(ii )–organic framework with a bis(triazole) ligand was prepared and employed to catalyze solvent-free ROP of caprolactone. Abstract : By utilizing a flexible fluorinated bis(triazole) ligand 1, 4-bis(1, 2, 4-triazole-1-ylmethyl)-2, 3, 5, 6-tetrafluorobenzene (Fbtx), a thermally and chemically stable cobalt(ii )-containing tungstovanadate-based metal–organic framework (MOF) [Co3 (Fbtx)5 (V2 W18 O62 )(H2 O)2 ]·26H2 O n (denoted as CZU-5) was synthesized and structurally characterized. The X-ray structural analysis revealed that CZU-5 features a three-dimensional (3-D) self-penetrated α-polonium cubic structure, which results from a 3-D 4-fold interpenetrated diamondoid [Co(Fbtx)] n network connected by the Wells–Dawson-type tungstovanadate clusters. Unexpectedly, the introduction of vanadium atoms as heteroatoms into the Dawson-type anion in polyoxometalate (POM)-based coordination polymers has not been reported to date. For the first time, the POM-based material was demonstrated to be an effective catalyst for the solvent-free ring-opening polymerization of ε-caprolactone. Moreover, the CZU-5 catalyst could be recycled up to five times with the retention of both catalytic activity and crystal structure.